The Influence of Medical Record Officers' Perceptions of the Quality of Medical Records On The Completeness of Filling Out Electronic Medical Resumes at RSUD Ajibarang - Sari, Arum Astika; Purwati, Desi; Marini , Budi (Procedia of Engineering and Life Science, 2024)
Medical record officers play an important role in improving the quality of medical records, officers must have good knowledge and understanding in the medical record unit. Completeness of medical resume filling is an aspect that can have an impact on the quality of medical records. Health professionals, including doctors, nurses, and other medical staff, use medical resume sheets to record patient information. Incomplete medical resumes can cause major problems for medical records, which must fill out medical resumes thoroughly in their capacity as health service providers. This study aims to determine how the influence of medical record officers' perceptions of the quality of medical records on the completeness of filling out electronic medical resumes at RSUD Ajibarang. This research method is descriptive quantitative with a cross sectional approach and the test conducted with the Chi Square test. The population and sample were medical record officers totaling 32 respondents and inpatient medical resume forms totaling 32 medical resumes. The results showed that 32 respondents had a good perception of 31 people and an unfavorable perception of one person. The results of the analysis showed that the perception of medical record officers about the quality of medical records on the completeness of filling out electronic medical records showed that the p-value of 0.000 <0.05, so that H0 was rejected and H1 was accepted. It can be concluded that there is an influence between the perception of medical record officers about the quality of medical records on the completeness of filling out electronic medical resumes at RSUD Ajibarang.